Philantrophy in Education of Religious Tolerance in Kurikulum Merdeka at Elementary School Temanggung District - Utomo, Sigit Tri; Ridwan, Muhammad; Amirudin, Yoyok; Nida, Dzikrina Khoirun; Yusuf, Ahmad; Tamama, Muna Badru (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
The multicultural Indonesian nation consisting of various tribes, languages, ethnicities, cultures, and religions must uphold tolerance education. including the implementation of the